A mathematical model to predict surface runoff under sprinkler irrigation conditions - Ghorbani, Behzad (Cranfield University, 1997)
Runoff from agricultural areas under sprinkler irrigation systems is a big problem. This is because runoff not only reduces water use efficiency (WUE), but also reduces soil fertility through depletion of fertilisers and pesticides, causes non uniformity of soil water content along the field slopes and ultimately reduces crop production and causes environmental pollution. Although sprinkler irrigation systems are usually designed so that the water application rate is less than the soil infiltration rate to avoid runoff, there are a growing number of sprinkler systems where runoff has become a serious problem. Large mobile single sprinklers (rainguns) which can irrigate large areas in a relatively short time are prone to severe runoff problems, because of the high application rates. Modern centre pivot and linear systems, which have now been designed to run at low energy saving pressures also produce high application rates and potential runoff. Most runoff problems are dealt with in the field on a trial and error basis. Being able to predict runoff under sprinkler irrigation would enable water application rate to be recommended and cultivation practices to be ‘designed’ rather than guessed on a trial and error basis in order to store surface water and avoid runoff. The objective of this study was to develop a mathematical model that can predict surface runoff from a small watershed area using sprinkler irrigation systems in either a stationary or moving condition. The objective was met in two ways: a mathematical model was developed from first principles called Overland Flow (OLF) and an existing model, KINEROS modified to EUROSEM, but designed for overland flow and soil erosion from hydrological watersheds was adapted to suit micro-catchment conditions for both stationary and moving sprinklers. Both models are based on kinematic wave theory. Both models were validated by laboratory and field experiments using stationary and moving sprinklers on simple plane and ridge and furrow cultivation practices. The validation results showed that the model predicts well the shape of the runoff hydrograph but also the key points for practical application. For example, time to start runoff, time to peak, peak flow rate, volume of runoff and time to end which are important when designing a cultivation practice in the field. The performance of the EUROSEM-KINEROS model was further evaluated by statistical techniques. There was good agreement between observed and model results. The EUROSEM-KINEROS model was also used to examine the best practical techniques to minimise the surface runoff. The application of this model to sprinkler irrigation design and management was also assessed. The evaluation results showed that the hydrograph parameters can be used to recommend water application rate, water application time and / or to design soil and water conservation structures to avoid critical situation in the field. Model validation for a moving sprinkler is recommended to be undertaken for different moving irrigators such as rainguns, centre pivot, side move systems and low energy precision application (LEPA) systems. Further investigations are also required to evaluate the use of the model to predict the effects of soil and water conservation techniques on runoff prevention for a cultivated land for different crops.